Meningkatkan Kemampuan Motorik Halus Anak Usia Dini Melalui Kegiatan Kolase Dengan Pelepah Pisang Dikelompok B TK Al Hidayah IX Pondokrejo Tempurejo Jember - Ro’ad, Dita Nurmala Ainur; Putra, Wijaya Adi; Sugiarto, Muhammad Agus (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to improve fine motor skills in early childhood through collage activities using banana stems. The researcher employed classroom action research (CAR) using the Kemmis and McTaggart model, which involves four stages: planning, implementation, observation, and evaluation. The research was conducted at Al Hidayah IX Kindergarten in Pondokrejo, Tempurejo, Jember, involving 30 students from group B. Data collection techniques included observation and documentation. The results showed that in the pre-cycle, 9 children (30%) achieved the expected developmental level. In the first cycle, 14 children (47%) reached this level, and in the second cycle, the number increased to 25 children (83%). Based on these findings, it can be concluded that collage activities using banana stems effectively enhance the fine motor skills of early childhood students, as evidenced by the results obtained at Al Hidayah IX Kindergarten in Pondokrejo, Tempurejo, Jember.